1988
DOI: 10.1111/j.1600-0714.1988.tb01331.x
|View full text |Cite
|
Sign up to set email alerts
|

The unicystic ameloblastoma: a clinicopathological study of 57 cases

Abstract: A clinicopathological study of 57 unicystic ameloblastomas has been undertaken, which represents 15% of all cases of ameloblastoma accessioned in our department over a 30‐yr period. Of the cases where gender was recorded: 30 were male and 23 female. The majority of patients were black (51 cases) and most occurred in the mandible (52). This distribution conforms to that of solid and multicystic ameloblastomas. The mean age at diagnosis was 23.8 years (S.D. 14.9) which is significantly younger than for the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
191
2
24

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(222 citation statements)
references
References 11 publications
5
191
2
24
Order By: Relevance
“…The text defines unicystic ameloblastoma using the criteria proposed in the original article by Robinson and Martinez [15] in 1977 and subdivides them into luminal and mural. The text does not acknowledge that subsequent authors have recommended that mural invasion should be viewed as conventional ameloblastoma [16][17][18]. Li et al [19] in 2000 reported a recurrence rate of 36 % with mural invasion in unicystic ameloblastomas and a recurrence rate of less than 10 % with the other subtypes.…”
Section: Epithelial Tumorsmentioning
confidence: 99%
“…The text defines unicystic ameloblastoma using the criteria proposed in the original article by Robinson and Martinez [15] in 1977 and subdivides them into luminal and mural. The text does not acknowledge that subsequent authors have recommended that mural invasion should be viewed as conventional ameloblastoma [16][17][18]. Li et al [19] in 2000 reported a recurrence rate of 36 % with mural invasion in unicystic ameloblastomas and a recurrence rate of less than 10 % with the other subtypes.…”
Section: Epithelial Tumorsmentioning
confidence: 99%
“…Most of the time ameloblastomas are asymptomatic and are first seen on a routine radiograph. As the lesion slowly enlarges the patient seldom notices it until it becomes obviously disfiguring [10]. Hence most of the patients report at later stage of the disease as in our case.…”
Section: Discussionmentioning
confidence: 53%
“…Ackerman et al [10] reviewed 57 cases of UA and found that nearly half of the patients were \20 years of age. Compared to multicystic ameloblastoma, unicystic variety occurs more commonly at younger age as in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At radiography these lesions appear as a well-defined, wellcorticated radiolucency resembling a dental cyst. 13 The biologic behavior is thought to be similar to that of the conventional ameloblastoma, but because few cases have been reported, the pathogenesis and clinical features are not yet fully understood and biologic behavior cannot be predicted.…”
Section: Smithmentioning
confidence: 99%